The Tale of Stridor and Wheezing in an Infant. (9th February 2021) - Muhammad, Umer; Shaffer, Marcus; Bishara, John
Abstract : Recurrent respiratory papillomatosis is a respiratory disease caused by human papillomavirus and can infect any part of the aerodigestive tract, but the larynx is most involved (Derkay et al. 2010). This report is a discussion about a 7-month-old male that presented to our institution for respiratory distress. He was admitted to the Pediatric Intensive Care Unit (PICU) for stabilization, observation, and further treatment and management due to an acute RSV infection. Initial efforts failed to improve his respiratory failure. A bronchoscopy was performed and showed various flesh-colored lesions throughout the larynx, vocal cords, and tracheal tree just above the carina. Pediatric otolaryngology performed an emergent debulking surgery to alleviate his respiratory failure. He has had multiple exacerbations of his condition since then and has required frequent debulking procedures with a few trials of intralesional bevacizumab therapies.